Change in implicit alcohol associations over time: Moderation by drinking history and gender. (August 2020) - Lindgren, Kristen P.; Baldwin, Scott A.; Peterson, Kirsten P.; Wiers, Reinout W.; Teachman, Bethany A.
Highlights: US college students' implicit alcohol associations increased over a 2-year period. Lifetime drinking history moderated changes in drinking identity associations. Greater increases were found in those without (vs. with) a history of intoxication. Gender moderated changes in implicit alcohol-excite associations. Greater increases were found in women (vs. men). Abstract: Implicit measures of alcohol-related associations or implicit alcohol associations are associated with drinking outcomes over time and can be understood as vulnerability markers for problem drinking. Longitudinal research remains rare, leaving open questions about how implicit alcohol associations themselves change over time and what factors moderate that change. We examined these questions with data from a larger study of first and second year U.S. college students. We investigated how these implicit alcohol associations change over time and potential moderators of those changes (gender, lifetime drinking history, family history of problem drinking, and class standing). A sample of 506 students (57% women) completed baseline demographic measures and implicit measures (variants of the Implicit Association Test [IAT]) assessing associations with drinking and the self [drinking identity], alcohol and excite [alcohol-excite], and alcohol and approach [alcohol-approach]). IATs were completed at 3-month intervals for a total of 8 assessments. Results indicated small, but significant, change in alcohol-excite and alcohol-approach IAT scores over time, and mixed findings for hypothesized moderators. Drinking history moderated change in drinking identity IAT scores, with increases over time among individuals with no history of drinking or no history of intoxication and decreases among individuals with a history of intoxication. Gender moderated change in alcohol-excite IAT scores with greater change among women (vs. men). No significant moderators of change in alcohol approach IAT scores were found. Results point to the importance of evaluating implicit associations' trajectories and identifying additional factors that predict those trajectories and concomitant vulnerability to problem drinking.